2017
DOI: 10.2147/lra.s111554
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory thyroidectomy: an anesthesiologist’s perspective

Abstract: Thyroidectomy has been performed on an inpatient basis because of concerns regarding postoperative complications. These include cervical hematoma, bilateral recurrent laryngeal nerve injury and symptomatic hypocalcemia. We have reviewed the current available evidence and aimed to collate published data to generate incidence of the important complications. We performed a literature search of Medline, EMBASE and the Cochrane database of randomized trials. One hundred sixty papers were included. Twenty-one papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…To improve the comfort of patients, anesthesiologists can effectively reduce the incidence of postoperative PONV by rationally selecting drugs and anesthesia methods during the operation. Studies have shown that moderate use of dexmedetomidine in thyroidectomy can reduce the use of postoperative anesthesia, which will help patients’ postoperative analgesia ( 22 , 23 ). However, the use of dexmedetomidine during overnight thyroidectomy did not reduce the incidence of PONV at 24 hours in postoperation (p=0.355) ( 24 ).…”
Section: The Associated Complicationsmentioning
confidence: 99%
“…To improve the comfort of patients, anesthesiologists can effectively reduce the incidence of postoperative PONV by rationally selecting drugs and anesthesia methods during the operation. Studies have shown that moderate use of dexmedetomidine in thyroidectomy can reduce the use of postoperative anesthesia, which will help patients’ postoperative analgesia ( 22 , 23 ). However, the use of dexmedetomidine during overnight thyroidectomy did not reduce the incidence of PONV at 24 hours in postoperation (p=0.355) ( 24 ).…”
Section: The Associated Complicationsmentioning
confidence: 99%
“…Steckler first introduced ambulatory thyroid surgery in 1986 (5). In recent years, improvements in surgical techniques have decreased the incidence of complications in thyroid surgery (6), and the use of ambulatory thyroid surgery has gradually increased. Many international reports have shown the safety and economic benefits of ambulatory thyroid surgery (7,8).…”
Section: Introductionmentioning
confidence: 99%